Efektivitas Penggunaan Modul Termokimia Berbasis Inkuiri Terbimbing Terintegrasi Eksperimen Terhadap Hasil Belajar Peserta Didik - Rahmatania, Finny; Andromeda, Andromeda; Rahim, Fanny Rahmatina (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2021)
Latar belakang: Chemistry learning in thermochemistry material has not been able to guide students to find concepts by themselves. Because of this, teaching materials are needed modules that apply the model-guided inquiry integrated experiment. Metode penelitian: This research aims to determine the effectiveness of uses a thermochemistry module based on guided inquiry integrated experiments with student learning outcomes. The type of this research was Randomized Pretest-poss test Control Group Design. The population was students of class XI MIPA SMAN 3 Padang, consist of 8 classes. The samples were chosen using a purposive-cluster random sampling technique, obtained XI MIPA 7 as experiment class and XI MIPA 4 as control class. Data analysis in this research was students learning outcomes in the cognitive domain. Hasil penelitian: The average value of the control class was 80,42 and the experiment class was 84,58. From the results statistic, both two sample classes had normal and homogenous. Based on the hypothesis using t-test with a significance level of 0,05 was found count was 3,32 and ttable was 1,66., which means H1 was accepted. In addition, to know the effectiveness of the thermochemistry module based on guided inquiry integrated experiment it can be seen using the N-Gain score. Kesimpulan: So it can be concluded that the module is effective in improving student learning outcomes in the XI MIPA at SMAN 3 Padang.